Evaluation of blood flow velocity envelope in common carotid artery for reference data - Noor Azmi, Azran Azhim; Ueno, Akinori; Tanaka, Masato; Akutagawa, Masatake; Kinouchi, Yohsuke (Elsevier Ltd, 2011)
The aim of the present study is to investigate the usefulness of envelope waveforms of blood velocity and its indices in the common carotid artery (CCA). The envelope waveforms are measured using a developed wireless measurement system. The CCA blood velocity waveforms of 202 healthy volunteers were analyzed. Multivariate analysis was used to determine the relationship between fixed factors and the selected hemodynamic data after adjusting for the fixed factors. The results revealed the effects of age, gender and exercise on the blood velocity waveforms in the CCA. The results suggest that evaluations of the envelope waveform indices are more reliable when these effects are accounted for. The normal blood velocity parameters in CCA are determined from 202 healthy subjects in the age range 20–69 years after adjusting for the effects of gender and exercise. The findings are expected to be a reference data for healthcare and clinical evaluations.